2016
DOI: 10.1016/j.fertnstert.2016.07.1092
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis: a national multicenter obstetric and neonatal follow-up study

Abstract: In this cohort study, the risk of adverse obstetric and neonatal outcomes was mainly related to the underlying parental condition rather than the PGD procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 24 publications
(22 reference statements)
10
49
0
1
Order By: Relevance
“…Additionally, the study did not account for variations in obstetrical management. Compared with spontaneously conceived pregnancies, labour following ART pregnancies is more frequently induced, which again may be explained by increased prevalence of obstetrical risk factors or complications, or as a consequence of anxiety or maternal request. However, if unaccounted for, it may introduce survivorship bias and underestimation of the true risk of stillbirth, as it may lead to comparison of pregnancies following spontaneous conception with the remaining ongoing uncomplicated IVF pregnancies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, the study did not account for variations in obstetrical management. Compared with spontaneously conceived pregnancies, labour following ART pregnancies is more frequently induced, which again may be explained by increased prevalence of obstetrical risk factors or complications, or as a consequence of anxiety or maternal request. However, if unaccounted for, it may introduce survivorship bias and underestimation of the true risk of stillbirth, as it may lead to comparison of pregnancies following spontaneous conception with the remaining ongoing uncomplicated IVF pregnancies.…”
Section: Discussionmentioning
confidence: 94%
“…Correspondingly, IVF has been associated with increased risk of induction of labour. 2,8 When evaluating the risk of stillbirth at a given gestational age associated with IVF, failure to account for induction of labour, or the reason hereof, may lead to underestimation of the true association, as it may give rise to comparison of pregnancies following spontaneous conception with the remaining on-going uncomplicated IVF pregnancies. Thus, for the uncomplicated majority of IVF pregnancies, the risk of stillbirth at term is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no difference in any perinatal outcome was observed in women aged more than 35 years according to PGD indication [134]. Another recent multicenter-cohort study confirmed that the risk of adverse perinatal outcomes was mainly related to the underlying parental conditions rather than the PGD procedure [135]. In fact, after stratification of data for PGD indication, adverse obstetric and neonatal outcomes were only present in children conceived by PGD due to parental monogenetic disorder but not in children conceived after PGD due to parental chromosomal aberrations [135].…”
Section: Resultsmentioning
confidence: 99%
“…Another recent multicenter-cohort study confirmed that the risk of adverse perinatal outcomes was mainly related to the underlying parental conditions rather than the PGD procedure [135]. In fact, after stratification of data for PGD indication, adverse obstetric and neonatal outcomes were only present in children conceived by PGD due to parental monogenetic disorder but not in children conceived after PGD due to parental chromosomal aberrations [135]. Nevertheless, there was a consistent risk of placenta previa (aOR 9.1, 95 % CI 3.4 to 24.9) after PGD and IVF/ICSI, suggesting that parental factors cannot explain all adverse outcomes [135].…”
Section: Resultsmentioning
confidence: 99%
“…Reports on neonatal outcomes and obstetrical complications of PGT pregnancies are limited. [76][77][78][79][80][81][82] Some studies have evaluated the effects of embryo biopsy without distinction between PGT-M and PGT-A. 77,80 It is necessary to consider that the technical procedures for PGT-M and PGT-A are similar, while the indication for these techniques is not.…”
Section: Obstetrical and Perinatal Outcomesmentioning
confidence: 99%